Mapping research on online gambling: a bibliometric analysis - Akat, Muhammed (Journal of Dependence, 2025)
This study aimed to conduct a bibliometric analysis of studies on online gambling. Web of Science Core database was used to obtain all publications on online gambling between 1998 and 2024. The bibliometric analysis was confined to studies published up to 2024, given that 2025 is still in progress and the complete body of literature for that year is not yet accessible. The bibliometric analysis was conducted using the VOSviewer program. The study initially determined that the number of studies in the domain of online gambling exhibited an overall increase from 1998 to 2024, with a few exceptions. A co-authorship analysis indicates that England is the most prolific nation in this field of study. Subsequently, Australia, Canada, the United States of America, and Spain are in descending order of productivity. The analysis yielded the conclusion that Nerilee Hing is the most influential researcher in the field of online gambling. The results of the cooccurrence analysis indicated that the most frequently used keywords were related to "gambling", "online gambling", "problem gambling", "responsible gambling", "addiction", "COVID-19", and "adolescent". In this study, it was concluded that research on online gambling addiction has increased over the years and that online gambling addiction has been emphasized in different cultures.